Association Between High Arterial Oxygen Tension and Long-Term Survival After Spontaneous Intracerebral Hemorrhage. Issue 1 (January 2016) - Fallenius, Marika; Raj, Rahul; Reinikainen, Matti; Bendel, Stepani; Skrifvars, Markus B.
Abstract : Objective: To determine the relation between high arterial oxygen tension levels (PaO2 ) and long-term mortality in patients with spontaneous intracerebral hemorrhage treated in the ICU. Design: National observational multicenter cohort study. Setting: Twenty-one ICUs in Finland. Patients: A total of 3, 033 adult patients. Interventions: None. Measurements and Main Results: Patients were divided into high (> 150 mm Hg), intermediate (97.5–150 mm Hg), and low (< 97.5 mm Hg) PaO2 groups based on the lowest measured PaO2 /FIO2 ratio during the first 24 hours after ICU admission: 63% ( n = 1, 923) were in the low group, 29% ( n = 892) were in the intermediate group, and 7% ( n = 218) were in the high group; 80% were mechanically ventilated. The primary outcome was 6-month mortality, which occurred in 49% of patients and was significantly more frequent in the high PaO2 group than in the intermediate and low PaO2 groups (61% vs 52% and 46%, respectively, p < 0.001). In univariate analysis, patients in the high PaO2 group had a significantly increased risk of 6-month mortality compared with the low PaO2 group (odds ratio, 1.82; 95% CIs, 1.36–2.42; p < 0.001), but this statistically significant relation was lost after adjusting for markers of severity of illness in a logistic mixed-effects regression model (odds ratio, 1.10; 95% CI, 0.76–1.60; p = 0.598). Conclusions: No significant relation between PaO2 levels and long-term mortality was found. The clinical role of hyperoxemia in patients with intracerebral hemorrhage treated in the ICU remains controversial and warrants further studies. Abstract : Supplemental Digital Content is available in the text.